LIMFOSIT PLASMA BIRU DAN JUMLAH LEUKOSIT PADA PASIEN ANAK INFEKSI VIRUS DENGUE DI MANADO - Arruan, Rosnatalia D.; Rambert, Glady; Manoppo, Firginia (Universitas Sam Ratulangi, 2015)
Abstract: Dengue is an arboviral disease that is widely spread across the world by Aedes mosquitoes. The early onset of dengue virus infection is difficult to identify due to indistinctive clinical symptoms. Therefore, simple laboratory test is required in the early diagnosis of dengue virus infection. Laboratory test that include routine blood test and blue plasma lymphocyte are important as rapid and relatively cheap diagnostic tool. Blue plasma lymphocytes derived from lymphoid which acts as an immune response that can be found in 4% of peripheral blood on 98% dengue hemorrhagic fever cases. Besides the increases in blue plasma lymphocytes, dengue virus infection can also causes leucopenia. Leucopenia in Dengue Hemorrhagic Fever (DHF) is characterized by the decrease of neutrophile count that happened during the early critical phase (third day of fever). This is a cross-sectional study using samples of 37 children who are infected with dengue virus in RS Advent Manado, RS TNI AD Wolter Monginsidi, RS Pancaran Kasih Manado during December 2014 to January 2015. Inclusion criteria are children below age 15, who have NS1 or IgG/IgM positive, who are on the third until seventh day of fever, whose parents or guardian have signed the informed consent. Conclusion: Leucopenia (leukocyte count below 4000/mm3) was found in children with dengue virus infection who had their routine blood test. Blue plasma lymphocytes are not always found in patients with NS1-AG, IgG/IgM positive.Keywords: dengue virus infection, leucocyte, blue plasma lymphocyteAbstrak: Dengue adalah penyakit arboviral yang paling banyak tersebar di dunia yang ditularkan nyamuk Aedes. Awal infeksi virus dengue sulit untuk dikenali sebab tidak menunjukkan gejala klinis khas. Karena itu, pemeriksaan laboratorium sederhana dapat berperan dalam pengenalan infeksi virus, adalah pemeriksaan darah rutin dan limfosit plasma biru yang cepat dan murah. Limfosit plasma biru sebagai respon imun dengan persentase 4% di darah tepi pada 98% kasus demam beradarah dengue. Selain peningkatan limfosit plasma biru, infeksi virus dengue juga dapat menyebabkan leukopenia. Leukopenia pada demam berdarah dengue didominasi penurunan jumlah neutrofil yang terjadi pada awal fase kritis (hari ketiga demam). Penelitian ini menggunakan desain cross sectional dengan sampel penelitian 37 pasien anak yang terinfeksi virus dengue di RS Advent Manado, RS TNI AD Wolter Mongisidi, RS Pancaran Kasih Manado pada bulan Desember 2014 sampai Januari 2015. Kriteria masukan adalah Anak usia kurang dari 15 tahun, hari ketiga sampai ketujuh demam, NS1 atau IgG/IgM positif, Orangtua atau wali bersedia menandatangani informed consent. Simpulan: Pada pasien anak dengan infeksi virus dengue yang dilakukan pemeriksaan darah rutin ditemukan adanya leukopenia dengan jumlah leukosit dibawah 4000/mm3.Kata kunci: infeksi virus dengue, leukosit, limfosit plasma biru